LEADER ENDORSEMENT: THE ROLE OF LEADER PROTOTYPICALITY, LEADER EFFECTIVENESS AND EMPLOYEE’S ORGANIZATIONAL IDENTIFICATION - Rochman, Taufik Nur; Samian, Samian; Riantoputra, Corina D. (Jurnal Psikologi, 2020)
Leadership occurs when the individuals claimed capable of leading, received endorsements from their subordinates. Without endorsements (i.e., subordinates’ willingness to support and be directed by the leader), no leader will be able to direct and influence their subordinates. Using the Social Identity Theory of leadership, this research aimed to investigate the factors influencing leader endorsement. Through an online survey with good internal consistency (i.e., coefficient reliability ranging from .7 to .9), this study was able to collect data from 186 private employees across Indonesia.  The moderated multiple regression analysis showed 1) subordinates tend to endorse prototypical leaders; 2) organizational identification is positively related to leader endorsement; and 3) leader effectiveness weakens the positive relationship between leader prototypicality and leader endorsement.  This study contributes to the social identity theory of leadership by demonstrating that low prototypical leaders may still get endorsed, as long as they are showing effective behavior.  This new finding sheds light on what kind of leadership behaviors may win the endorsement from their subordinates.